On-Chip Inverse Designed Fabry-Pérot Resonators - Bi, Toby; Zhang, Shuangyou; Ghosh, Alekhya; Lohse, Olga; Harder, Irina; Yang, Ki Youl; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Silicon nitride (Si3N4) is emerging as the forerunner for integrated photonic microresonator devices due to its wide transparency window from 0.47 to 6.7 µm, relatively large third-order nonlinearity, and a complementary metal-oxide semiconductor compatible fabrication process that ensures low propagation losses. The advances in the Si3N4 platform have led to tremendous growth in the fields of optical telecommunications, spectroscopy, and astronomical instrument calibration. Traditional on-chip microresonators are waveguide ring resonators that are evanescently coupled via a bus waveguide. Recently, a paradigm shift towards on-chip Si3N4 microcavities based on the Fabry-Pérot resonators has emerged [1,2]. These cavities can be formed when a central waveguide has two Bragg-like reflectors on either side. One advantage of using a linear cavity is gaining extra degrees of freedom for dispersion engineering through sub-micron structuring of the reflectors. In this work, we use broadband inverse-designed reflectors [3,4] to realize high-Q on-chip linear Si3N4 microresonators.
CRIS-Team Scopus Importer:2024-12-16